Periodontal health intervention for oral health-related outcomes in older type 2 diabetes patients: a randomized controlled trial in a Chinese tertiary hospital - Chunxiu Xiao; Lan Zhang; Zhaoxi Li; Qingnv Xu; Suping Lin; Siyu Zheng; Hanping Shi (Scientific Reports)
Abstract As the sixth complication of diabetes, periodontitis interacts with diabetes to form a vicious circle. Periodontal health interventions can improve periodontal health and the quality of life in older patients with type 2 diabetes mellitus (T2DM). This study aimed to explore the effect of periodontal health interventions based on the Pender Health Promotion Model on periodontal outcome index and quality of life in this patient population. This randomized controlled trial enrolled 108 patients with T2DM from the endocrine and metabolism department of a tertiary hospital. Participants were randomly assigned to either an experimental group or a control group. The control group received routine diabetes health education and periodontal health-related knowledge education, they were general diabetes management and standard dental hygiene instructions. While the experimental group underwent a periodontal health intervention program in addition to the routine health interventions, it focuses on a combination of individualized and targeted comprehensive assessments, professional training, patient education, and behavioral interventions. Relevant outcome measures were assessed at baseline and after 12 weeks of intervention. The main outcomes were oral hygiene-related measures, including dental plaque, debris and calculus conditions, the secondary outcomes included subjective assessment of oral health and self-assessment of knowledge, attitude and behavior. Demographic questionnaires, Plaque Index (PLI), Geriatric Oral Health Assessment Index (GOHAI), Periodontal Health Knowledge, Attitude, and Behavior Questionnaire, as well as the Oral Hygiene Index-Simplified (OHI-S) (including Debris Index-Simplified (DI-S) and the Calculus Index-Simplified (CI-S)) were used to collect data. Statistical analysis was performed using Chi-square tests, Fisher’s exact tests, and SPSS software version 27. A p-value of < 0.05 was considered statistically significant for all tests. Following the intervention, significant differences were identified between the groups in PLI, OHI-S, and Periodontal Health Knowledge, Attitude, and Behavior (P < 0.05). However, there was no significant difference in GOHAI scores between the groups (P > 0.05). Based on the results of this study, it can effectively prevent the occurrence or progression of periodontitis, as well as enhance periodontal health knowledge, attitudes, and behaviors while positively impacting the oral health index and quality of life of older patients with T2DM. This approach holds significant value in medical practice and provides strong support for the widespread promotion of periodontal health maintenance strategies.